PENGEMBANGAN DAN VALIDASI METODE KROMATOGRAFI CAIR KINERJA TINGGI PADA ANALISIS ANDROGRAFOLIDA DALAM BAHAN BAKU DAN TABLET FRAKSI ETIL ASETAT Andrographis paniculata . - BACHTIAR RIFAI PRATITA IHSAN, NIM 051414153010 (2016)
Ethyl acetat fractions from Andrographis paniculata has been developed as phytopharmaceutical products. Andrographolide which is the major active compound of Andrographis paniculata was determined as marker compund of ethyl acetate fractions of Andrographis paniculata products. To ensure the quality, efficacy and safety of the phytopharmaceutical products, a simple and selective analytical method becomes important for the determination of andrographolide in both the raw materials and products. The purpose of this study was to develop and validate a simple and selective High Performance Liquid Chromatography (HPLC) for determination andrographolide in raw material and tablet etil acetate fractions Andrographis paniculata. This method was performed using a RP-C18 Column (3.0 x 50 mm i.d., 2.7μm parcticle size) as stationary phase, column temperature was maintained at 30⁰C, isocratic mobile phase of metanol : water (pH 3.05 with phosporic acid) (50:50 v/v) mobile phase with flow rate of 0.3 ml/menit, injection volume 0,5μl and detected at 228 nm. The results showed that method was selective to separate andrographolide peak from other component with good resolution, retention time andrographolide was 2,5 minute. The data for calibration plots showed good linear relationship with r2 = 0.9996 in the concentration range 50-1000 ppm. The limit of detection and Quantification were found 4.89 ppm and 16.19 ppm, respectively. The recovery method was found between 93.76 and 101.72% and the relative standard deviation method was found between 1.60% and 2.39%.